PEMANFAATAN GOOGLE CLASROOM DAN GOOGLE MEET SEBAGAI MEDIA PEMBELAJARAN ONLINE PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM KELAS XI SMAN 01 MALANG DI MASA PANDEMI COVID-19 - Muchammad Aziz Kurniawan; Ika Ratih Sulistiani; Lia Nur Atiqoh Bela Dina (VICRATINA, 2021)
The spreads of Covid-19 in many countries has made major changes in various fields, especially education. Based on the Ministry of Educations and Culture circular letter Numbers 4 year 2020th about procedur implementation education policies in the emergency period of Covid-19, it is explained that the process of learning activities is carried out at home through online/distance learning. In this study it was found that the efforts made by Islamic Religious Education teachers to class XI students at SMAN 01 Malang were by utilizing Google Classroom and Google Meet as online learning media. Therefore, the purpose research to describe planning, implementation, and evaluation of the use of Google Meet and Google Classroom in online learning of Islamic Religious Education at SMAN 01 Malang. This research uses a qualitative and case study. The data collection methods are observation, interview, and documentation. The planning is done by changing the previous lesson plan and making one sheet lesson plan adapted to online learning every week. In its implementation, it is adjusted to the lesson plan that was made at the beginning and is divided into three: preliminary, core, and closing stages. Student learning outcomes are good but not all of them are good, there are scores that are still below the average. Evaluation in the use of google meet and google classroom in online learning of Islamic Religious Education at SMAN 01 Malang conducted by the teacher is an assessment to determine the level of student development in learning.